Correlation of SARS-CoV-2 Viral Load and Clinical Evolution of Pediatric Patients in a General Hospital From Buenos Aires, Argentina - Martín Eduardo Brizuela; Sandra Elizabeth Goñi; Georgina Alexandra Cardama; María Alejandra Zinni; Alejandro Andres Castello; Leandro Matías Sommese; Hernán Gabriel Farina (Frontiers Media S.A., 2022)
BackgroundSARS-CoV-2 infection is associated with a wide range of clinical manifestations and severity. Pediatric cases represent <10% of total cases, with a mortality rate below 1%. Data of correlation between SARS-CoV-2 viral load in respiratory samples and severity of disease in pediatric patients is scarce. The cycle threshold (CT) value for the detection of SARS-CoV-2 could be used as an indirect indicator of viral load in analyzed respiratory samples.ObjectiveThe aim of this study was to describe CT values and their correlation with clinical manifestations, epidemiology and laboratory parameters in pediatric patients with confirmed COVID-19.MethodsIn this observational, retrospective, analytic and single-center study we included patients under 15 years with confirmed COVID-19 by RT-PCR SARS-CoV-2 admitted to the Isidoro Iriarte Hospital (Argentina) between March 1st 2020 and April 30th 2021.Results485 patients were included, the distribution according to disease severity was: 84% (408 patients) presented mild disease, 12% (59 patients) moderate disease and 4% (18 patients) severe disease. Patients with moderate and severe illness had an increased hospitalization rate, prolonged hospitalization, higher frequency of comorbidities and oxygen and antibiotics use. CT values, that could be used as an indirect measure of viral load, was associated with severity of clinical manifestations and age under 12 months. No patient required admission to PICU nor mechanical ventilation. No deaths were registered.ConclusionsIn this study, the viral load of SARS-CoV-2 in respiratory samples, determined by the cycle threshold, was significantly correlated with moderate to severe cases and with age.